PEDAGOGICAL POSSIBILITIES OF DISTANCE LEARNING IN THE HIGHER EDUCATION SYSTEM (Universal International Scientific Journal, 2026)
The article covers the essence of distance learning, didactic foundations, pedagogical principles, interactivity, individualization, differentiation, independent learning, reflection, and control. It also explains the role of electronic platforms, digital resources, video lessons, forums, testing systems, and virtual collaboration tools in organizing distance learning.
Keywords: distance learning, higher education, pedagogical opportunities, digital learning, e-learning, independent learning, interactivity, individualization, educational technologies, virtual learning environment, LMS, online learning